2020
DOI: 10.3390/met11010044
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of the Effect of Atmospheric Corrosion Induced Hydrogen on Mechanical Properties of Advanced High Strength Steel

Abstract: Hydrogen absorption into steel during atmospheric corrosion has been of a strong concern during last decades. It is technically important to investigate if hydrogen absorbed under atmospheric exposure conditions can significantly affect mechanical properties of steels. The present work studies changes of mechanical properties of dual phase (DP) advanced high strength steel specimens with sodium chloride deposits during corrosion in humid air using Slow Strain Rate Test (SSRT). Additional annealed specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Tensile strength [8], yielding strength [9], crack propagation [10,11,12], fatigue life [13,14,15] are main mechanical properties that is affect by corrosion when the materials are exposed to aggressive mediums such as acidic [16] and saline [7,17]. Corrosion effect on mechanical behavior of materials were studied experimentally [18] and/or numerically [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile strength [8], yielding strength [9], crack propagation [10,11,12], fatigue life [13,14,15] are main mechanical properties that is affect by corrosion when the materials are exposed to aggressive mediums such as acidic [16] and saline [7,17]. Corrosion effect on mechanical behavior of materials were studied experimentally [18] and/or numerically [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, Rudomilova observed that dual phase steel demonstrated a reduction in properties of tensile strength and elongation because corrosion caused a decrease in cross-sectional area of the specimens and pitting was formed. On the other hand, Rudomilova demonstrated that hydrogen absorption for 27 days is inadequate to affect the mechanical properties [8]. Li et al investigated corrosion effect on G250 mild steel used in bridge under stressed and non-stressed cases.…”
Section: Introductionmentioning
confidence: 99%
“…For investigation of hydrogen embrittlement, different test methods exist. Tests regarding the influence of diffusible hydrogen on degradation of different microstructures and steels are mainly carried out on electrochemically hydrogen charged tensile specimens [28][29][30][31]. When it comes to welding, there are numerous self-restraint and externally loaded test procedures for investigating HAC [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially a variation on a conventional tensile test (often abbreviated in the context of hydrogen research to CSRT, or 'conventional strain-rate test'), this involves running a tensile test upon a prefabricated and hydrogen-charged specimen at a strain-rate sufficiently low to allow hydrogen atoms to diffuse to high-stress regions, with a resultant loss of ductility and premature failure. Hydrogen charging can be performed in gaseous hydrogen [141], under atmospheric corrosion conditions [139,142], or, commonly, under imposed electrochemical charging conditions [136,140,143], and can be performed in situ during straining, or ex situ, prior to charging, or with a combination of both. Quantifying embrittlement is typically done via an assessment of the reduction in ductility during hydrogen-charged tests, such as decreases in total elongation at failure, reduction in cross-sectional area of the fracture surface, or the reduction in area under the tensile curve (absorbed energy), or may be assessed through the resultant decrease in test time-to-failure as a result of hydrogen ingress.…”
Section: Characterising Mechanical Degradationmentioning
confidence: 99%